Avaliação da vida útil de cabos condutores de alumínio com alma de aço utilizados em linhas aéreas de subtransmissão e transmissão de energia elétrica - Beline Quintino de Araujo Fonseca (2008)
This work presents a study of life estimation of Aluminum Conductors Steel Ucinlbrccil - AC-'SR used in overhead transmission lines, considering factors of iniluenee with respect to tensile strength. In addition, it presents the results of an implemented methodology used to estimate the conductor life. The proposed methodology integrates survey data of e.xisting lines, such as mechanical strength and hardness, data from operation and maintenance (transniiltcd i urreiits and maintenance occuirences) and environment data (temperature and wind velocity) ol the crossed regions. Resuh conelation is performed through a computational tool which considers the history of the line for estimating the remaining life of the conductor. 'I'he implenicnted methodology cai»be used to subsidize upgrade viability studies, plamiing of predictive mainlenance of existent conductors, period fo predictive maintenance for new conductors, overhead inspections usinj', helicopter with thermal-vision equipment to check the breakage ol" Aluminum stranils, and analysis of the actual state of the conductor in terms of public safely.